Serum glucose concentration in subacute intoxication with chlorpyrifos - Organophosphate insecticide - Anna Łukaszewicz-Hussain (Nofer Institute of Occupational Medicine, 2013)
Background: Epidemiological studies suggest that exposure to organophosphate insecticides enhances the risk of various diseases, including neurological disorders, e.g. Parkinson's or Alzheimer's disease, arteriosclerosis and diabetes mellitus. For this reason the aim of the presented study was to estimate serum concentration of glucose in subchronic intoxication with low doses of chlorpyrifos, an organophosphate insecticide. Materials and Methods: The rats received chlorpyrifos at a daily dose of 0.2, 2 or 5 mg/kg b.w./day for 14 or 28 days. For biochemical determinations of serum glucose in the rats ready-to-use kit was applied. Results: In subacute intoxication with chlorpyrifos the increased serum concentration of glucose was observed after 14 days of intoxication with the highest dose (5 mg/kg b.w.) and after 28 days of intoxication with all dose levels used. Conclusions: The results of this study showing the increased concentration of serum glucose in subacute intoxication with low doses of chlorpyrifos, as well as the literature data suggest that exposure to organophosphate insecticides can increase the risk of diabetes mellitus. It may thus be concluded that people occupationally exposed to these compounds should be subjected to diagnostic tests for early detection of diabetes. Med Pr 2013;64(4):527-531